Leadership of the Village Head in the Implementation of Duties and Functions of Ulobua Village Officials, Tibawa District, Gorontalo Regency - Nuriyanti S Nani; Lisda Van Gobel; Tety Thalib (Formosa Journal of Science and Technology, 2023)
This study aims to determine the Leadership of the Village Head in the Implementation of Duties and Functions of the Ulobua Village Apparatus. This research consists of three focuses, namely managerial ability, effective communication and leadership assertiveness. The research method used is descriptive qualitative. The results showed that the leadership of the village head in the implementation of the duties and functions of the Ulobua Village Apparatus was not optimal. This can be seen from the managerial ability of the Ulobua Village Head who has not been able to direct and mobilize village officials to work based on the main tasks and functions, the ability to communicate effectively which is still lacking by using a one-way communication pattern, and the firmness of the leadership in this case the Ulobua Village Head who is still less and each is easily influenced by outside parties.